An Application Layer Protocol to Support Cooperative Navigation of Multiple UAVs Systems - Basso, Maik; Vinel, Alexey; Pignaton de Freitas, Edison (Electronic Communications of the EASST, 2021)
Applications involving multiple UAVs have gained increasing relevance in recent years, due to the benefits that cooperative systems tend to provide to their applications. In addition to performing several simultaneous tasks, the time spent to perform a certain task is reduced. In this article, an architecture for sharing navigation information is demonstrated to support applications composed of systems with multiple UAVs.